Physicochemical Properties of Starch of Intermediate-Amylose and Waxy Rices Differing in Grain Quality - Merca, F.E.; Juliano, Bienvenido O. (Wiley, 1981)
Starches from two crops of 7 intermediate‐amylose and 7 waxy milled rices differing in eating qualities were characterized. Among the nonwaxy rice starches, those of softer cooked rice had gelatinization temperature of ≥ 70°C, medium to soft gel (110 mg/2 ml) consistency, low alkali viscograph peak viscosity, and greater Amylograph breakdown and lower Amylograph setback and consistency than low gelatinization temperature starches. Among waxy starches, gels of low gelatinization temperature samples had greater freeze‐thaw stability than gels of high gelatinization temperature samples. A 12% paste gave better differentiation in Amylograph viscosity than 10% paste of intermediate‐amylose milled rice. Water‐extractable substances that suppressed the Amylograph viscosity of milled waxy rices were lipids and polysaccharides.